Debunking the Myth of ‘Super Bowl Sex Trafficking’: Media hype or evidenced-based coverage - Martin, Lauren; Hill, Annie (Anti-Trafficking Review, 2019)
A large body of scholarship has described the narrow set of media narratives used to report trafficking for sexual exploitation to the public. This article examines US media coverage of human trafficking in relation to the Super Bowl, American football’s championship game. Available empirical evidence does not suggest that major sporting events cause trafficking for sexual exploitation. Yet, we find that 76 per cent of US print media from 2010 to 2016 propagated the ‘Super Bowl sex trafficking’ narrative. Local coverage of the 2018 Super Bowl in Minneapolis, Minnesota, was different, presenting a sceptical stance toward this narrative. The article describes how this substantial shift resulted from our research group and anti-trafficking stakeholders employing an action research approach to craft a Super Bowl communication strategy that aligned with empirical evidence. Although sensationalist narratives are difficult to dislodge, the Minnesota case shows that evidence on trafficking can be effectively used to inform media and impact public perceptions, when researchers work with stakeholders on the ground. Lessons learnt are shared to enable others to replicate these results.